Analisis Kinerja dan Keberlanjutan Implementasi Usaha Minyak Wijen “Wijen Natura” di Kota Palembang - Aldi Primatama; Steven Pranata Suryanto; Yulizar Kasih (MDP Student Conference, 2026)
This study aims to analyze the business performance and sustainability of Wijen Natura, a sesame oil business operating in Palembang City. The business utilizes local sesame seeds as the main raw material and applies a hot infusion method to produce high-quality sesame oil. The research method used is descriptive quantitative and qualitative approaches. Data were collected through consumer questionnaires, interviews with business owners, and analysis of financial reports and sales data. The results indicate that Wijen Natura has strong market potential in terms of consumer interest, sales growth, and business feasibility analysis. Appropriate marketing strategies, product quality, and flavor innovation are key factors in maintaining business sustainability. Based on financial and non-financial analysis, Wijen Natura is considered feasible and sustainable for further development.